Analisis Konflik dalam Perspektif Freud dan Relevansinya dengan Pabrik Semen di Rembang - Puryanto, Sidik (Mahesa Research Center, 2022)
This study aims to analyze the conflict of Sigmund Freud's perspective and it’s relevance to the cement factory in Rembang. This research method used a case study qualitative approach. The informants of this research consisted of 20 people, both from the support and contra of the cement factory. The data collection used unstructured interviews. Data analysis used three steps from Miles and Huberman. The results of this study indicate (1) human characters in conflict are divided into three categories, namely the id, ego and superego, which in Fisher's language are also referred to as stages of conflict; (2) the cement factory conflict in Rembang, seen from the emotional pattern, contains three group characteristics, namely the silent group, the moving group and the resisting group. The conclusion of this study showed that each conflict will experience escalation depending on the pattern of emotions. The emotions increase along with the contradictory productivity of conflict issues.